THE PROTECTION OF HUMAN RIGHTS FOR THE ASIAN DIASPORA IN SOUTHEAST ASIA AND ERADICATION MAFIA OF TRADE PEOPLE - Ma’rifah Ma’rifah; Muhammad Najmi Fajri (Jantera Hukum Bornea, 2022)
The Indonesian Diaspora Reality, which is a networked Community and strengthens with the potential of human resources which, not only is large, but "the selected few", Demanding a new political and human rights paradigm of citizenship for Indonesia. Double Citizenship Advocacy (Dwi Citizenship) requires steps as part of the largest democracy in the world. Moreover, the struggle for Dual Citizenship must be interpreted as a struggle to ensure the realization of human rights protection, especially for Indonesian diaspora children and women and the intelligent attitude of the Indonesian people and national policy makers in articulating the phenomenon and national policy-making in policies that are conducive to sustainability Indonesian national ideas and goals. Dual Citizenship issues are now increasingly developing. For those who support, have the view that Dual Citizenship for the government includes: a. Can improve economic relations between two countries; b. Expanding the economic base; c. Encouraging the development of trade, investment that opens employment; d. Dual Citizenship holders influence economic and political decisions in the country where they are domiciled, in such a way that decisions made can benefit the Republic of Indonesia; e. Dual citizenship will become a binder and avoid losing talented, intellectual and highly educated experts; f. Dual Citizenship is very good at supporting investment in Indonesia; g. Dual citizenship can introduce Indonesian culture abroad. Conversely, several reasons for those who reject the concept of Dual Citizenship include: a. Loyalty Problems; b. State Defense Obligations; c. Problems of Nationalism; d. Political rights; e. Land rights; f. Rights and obligations of citizens. Therefore the author uses a comparative approach to legislation both in force in Singapore, Malaysia and Indonesia related to the application of Double Citizenship